Reduction of synthetic stainless steel slags by aluminium. (2nd January 2019) - Lin, Yong; Chou, Kuo-chih; Scheller, Piotr; Shu, Qifeng
ABSTRACT: One of the most efficient ways to eliminate the harm of chromium oxide in stainless steel slag is to reduce chromium oxide in stainless steel slag using aluminium. In the present work, the Al reduction of synthetic CaO–SiO2 –Al2 O3 –MgO–Fe2 O3 –Cr2 O3 stainless steelmaking slags at different conditions, including temperature, slag basicity and Al amount was investigated to get optimal conditions for the reduction and the metal–slag separation. It was found that the agglomeration of metal droplets and metal–slag separations were improved by increasing temperature. The reduction degrees of SiO2, Fe2 O3 and Cr2 O3 were enhanced with increasing basicity of slag. The addition of CaF2 in slag leads to better agglomerations of metal droplets and metal–slag separations. The highest reduction degree of chromium could reach 99% in slag with basicity of 2 at 1873 K.